Music Self-Efficacy for Performance: An Explanatory Model Based on Social Support - Zarza-Alzugaray, Francisco Javier; Casanova, Oscar; McPherson, Gary E.; Orejudo, Santos (Frontiers in Psychology, 2020)
Personal perceptions of self-efficacy are particularly relevant in the field of music performance, which is oriented toward the outward expressions of one’s own ability through public performances. Within this context, a number of personal variables, including social support and performance anxiety, have been shown to be associated with musical success and are therefore relevant for research that seeks to understand the four sources of self-efficacy (mastery experiences, vicarious observation, verbal persuasion, physiological states) that are integral components of Bandura’s (2002) Social Learning Theory. Previous research, as well as observed differences among musicians associated with educational level (preuniversity) and gender (male/female), underpins the context of this study, which presents evidence regarding the factors that are capable of mediating perceptions of self-efficacy for musical performance. Specifically, the main objectives of this study were to more clearly understand relations between social support, public performance, musical performance anxiety, and self-efficacy using structural equation modeling and to compare these results according to gender. A battery of questionnaires was submitted to 359 preuniversity Spanish music students. Results highlight the relevance of family support for self-efficacy in public performance: directly and mediated through musical performance anxiety. The role of teachers and peers appeared to be relevant only for boys and was mediated through performance anxiety. Public performances lead to a greater degree of musical self-efficacy, but only in girls. Further research shall be required in order to improve pedagogical methods and help teachers increasingly individualize their teaching.